Eating for 3.8 × 1013: Examining the Impact of Diet and Nutrition on the Microbiota-Gut-Brain Axis Through the Lens of Microbial Endocrinology - Lyte, Joshua M. (Frontiers in Endocrinology, 2019)
The study of host-microbe neuroendocrine crosstalk, termed microbial endocrinology, suggests the impact of diet on host health and microbial viability is, in part, reliant upon nutritional modulation of shared host-microbe neuroendocrine axes. In the 1990’s it was first recognized that neuroendocrine pathways are major components of the microbiota-gut-brain axis, and that diet-induced changes in the gut microbiota were correlated with changes in host behavior and cognition. A causative link, however, between nutritional-induced shifts in microbiota composition and change in host behavior has yet to be fully elucidated. Substrates found in food which are utilized by bacteria in the production of microbial-derived neurochemicals, which are structurally-identical to those made by the host, likely represent a microbial endocrinology-based route by which the microbiota causally influence the host and microbial community dynamics via diet. For example, food safety is strongly impacted by microbial production of biogenic amines. While microbial-produced tyramine in cheese can elicit hypertensive crises, microorganisms which are common inhabitants of the human intestinal tract can convert L-histidine found in common foodstuffs to histamine and thereby precipitate allergic reactions. Hence, there is substantial evidence suggesting a microbial endocrinology-based role by which the gastrointestinal microbiota can utilize host dietary components to produce neuroactive molecules that causally-impact the host. Conversely, little is known regarding the reverse scenario whereby nutrition-mediated changes in host neuroendocrine production affect microbial viability, composition, and/or function. Mechanisms in the direction of brain-to-gut, such as how host production of catecholamines drives changes in microbial growth and functionality within the gut requires greater examination considering well-known nutritional effects on host stress physiology. As dietary-intake mediates changes in host stress, such as the effects of caffeine on the hypothalamic-pituitary-adrenal axis, it is likely that nutrition can impact host neuroendocrine production to affect the microbiota. Likewise, the plasticity of the microbiota to changes in host diet has been hypothesized to drive microbial regulation of host food preference via a host-microbe feedback loop. This review will focus on food as concerns microbial endocrinology with emphasis given to nutrition as a mediator of host-microbe bi-directional neuroendocrine crosstalk and its impact on microbial viability and host health.